The relationship between exercise‐induced muscle fatigue, arterial blood flow and muscle perfusion after 56 days local muscle unloading. (7th October 2013) - Weber, Tobias; Ducos, Michel; Mulder, Edwin; Beijer, Åsa; Herrera, Frankyn; Zange, Jochen; Degens, Hans; Bloch, Wilhelm; Rittweger, Jörn
Summary In the light of the dynamic nature of habitual plantar flexor activity, we utilized an incremental isokinetic exercise test (IIET) to assess the work‐related power deficit (WoRPD) as a measure for exercise‐induced muscle fatigue before and after prolonged calf muscle unloading and in relation to arterial blood flow and muscle perfusion. Eleven male subjects (31 ± 6 years) wore the HEPHAISTOS unloading orthosis unilaterally for 56 days. It allows habitual ambulation while greatly reducing plantar flexor activity and torque production. Endpoint measurements encompassed arterial blood flow, measured in the femoral artery using Doppler ultrasound, oxygenation of the soleus muscle assessed by near‐infrared spectroscopy, lactate concentrations determined in capillary blood and muscle activity using soleus muscle surface electromyography. Furthermore, soleus muscle biopsies were taken to investigate morphological muscle changes. After the intervention, maximal isokinetic torque was reduced by 23·4 ± 8·2% (P<0·001) and soleus fibre size was reduced by 8·5 ± 13% (P = 0·016). However, WoRPD remained unaffected as indicated by an unchanged loss of relative plantar flexor power between pre‐ and postexperiments (P = 0·88). Blood flow, tissue oxygenation, lactate concentrations and EMG median frequency kinematics during the exercise test were comparable before and after the intervention, whereas the increase of RMS in response to IIET was less following the intervention (P = 0·03). In conclusion, following submaximal isokinetic muscle work exercise‐induced muscle fatigue is unaffected after prolonged local muscle unloading. The observation that arterial blood flow was maintained may underlie the unchanged fatigability.